2017
DOI: 10.1111/cen.13363
|View full text |Cite
|
Sign up to set email alerts
|

Serum phosphorus levels and fracture following renal transplantation

Abstract: Fracture was common post-renal transplantation. Lower serum phosphorus levels and declining FN T-scores were associated with fractures. The mechanism of this previously unreported observation requires further evaluation in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
1
9
0
1
Order By: Relevance
“…Accepting these facts may help us to understand the importance of phosphate in kidney disease. Moreover, in kidney post transplants population, the association between some degrees of hypophosphatemia and fractures has been reported [36]. Remarkably, our results suggested that peripheral vascular calcification assessed by Adragao Score (hands) is related to VF.…”
Section: Discussionsupporting
confidence: 59%
“…Accepting these facts may help us to understand the importance of phosphate in kidney disease. Moreover, in kidney post transplants population, the association between some degrees of hypophosphatemia and fractures has been reported [36]. Remarkably, our results suggested that peripheral vascular calcification assessed by Adragao Score (hands) is related to VF.…”
Section: Discussionsupporting
confidence: 59%
“…FGF‐23 levels decline following transplantation and tend to normalise by 12 months, and together with reductions in PTH levels, there is concurrent stabilisation of phosphate levels . Persistent hypophosphataemia has been reported in the presence of ongoing elevated PTH levels, and there has been a report of increased fracture rates in renal transplant patients with lower serum phosphate levels . However, the long‐term consequences of low serum phosphate post‐transplantation on bone metabolism and fracture remain to be established …”
Section: Bone Health In Patients With Chronic Kidney Disease–mineral mentioning
confidence: 99%
“…72 Persistent hypophosphataemia has been reported in the presence of ongoing elevated PTH levels, 72,73 and there has been a report of increased fracture rates in renal transplant patients with lower serum phosphate levels. 74 However, the long-term consequences of low serum phosphate posttransplantation on bone metabolism and fracture remain to be established. 72 Low-turnover bone states may improve many years following transplantation with restoration of PTH levels, but ABD remains common.…”
Section: Renal Transplantationmentioning
confidence: 99%
“…Unpublished data from the COSMOS study (Current management Of Secondary hyperparathyroidism: a Multicentre Observational Study) are in the same line, showing, in a period of 3-year follow-up, that high serum phosphate is associated with a higher incidence of bone fractures. By contrast, Aleksova et al [81] found that low serum phosphate was associated with a higher risk of bone fractures in transplanted patients.…”
Section: Bone Biomarkersmentioning
confidence: 90%